2017
DOI: 10.1016/j.gdata.2017.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic vesicles isolated from the electric organ of Torpedo californica and from the central nervous system of Mus musculus contain small ribonucleic acids (sRNAs)

Abstract: Synaptic vesicles (SVs) are presynaptic organelles that load and release small molecule neurotransmitters at chemical synapses. In addition to classic neurotransmitters, we have demonstrated that SVs isolated from the Peripheral Nervous Systems (PNS) of the electric organ of Torpedo californica, a model cholinergic synapse, and SVs isolated from the Central Nervous System (CNS) of Mus musculus (mouse) contain small ribonucleic acids (sRNAs; ≤ 50 nucleotides) (Scientific Reports, 5:1–14(14918) Li et al. (2015) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Secretory vesicles are produced along the regulated secretory pathway and store soluble proteins, peptides or low molecular weight (MW) neurotransmitters. Very recent studies have demonstrated that they may also contain small ribonucleic acids (sRNAs), at least in the electric organ of Torpedo californica and in mouse synapses (Kim et al, 2015 ; Li et al, 2015 , 2017 ; Gümürdü et al, 2017 ). Once assembled, secretory vesicles are actively transported to specific subcellular domains for extracellular delivery in response to appropriate signals.…”
Section: State Of Art On High Molecular Weight Neurotransmitter Localmentioning
confidence: 99%
“…Secretory vesicles are produced along the regulated secretory pathway and store soluble proteins, peptides or low molecular weight (MW) neurotransmitters. Very recent studies have demonstrated that they may also contain small ribonucleic acids (sRNAs), at least in the electric organ of Torpedo californica and in mouse synapses (Kim et al, 2015 ; Li et al, 2015 , 2017 ; Gümürdü et al, 2017 ). Once assembled, secretory vesicles are actively transported to specific subcellular domains for extracellular delivery in response to appropriate signals.…”
Section: State Of Art On High Molecular Weight Neurotransmitter Localmentioning
confidence: 99%